Heat transfer process simulation for tuna freezing in 3 star refrigerator (-18Deg C) - Le Thanh Nien (Journal of Technical Education Science, 2017)
The advancement of science and engineering requires engineers to make more complex, expensive projects that require the highest levels of accuracy, safety and optimization. Such requirements are also required in thermal engineering especially for calculating the heat transfer equipment and optimal heat transfer process. This paper presents the results of calculating heat transfer for tuna freezing at temperature (-180C) by the software Comsol Multiphysics simulation and experimental results to verify the simulation results. The default task is to identify changes in temperature and time of freezing tuna in the refrigerator in accordance with the ambient temperature, the sample size of fish and freezing wind velocity. When comparing the theoretical calculation results and experimental measurements, the authors found that the surface and center temperature of the fish samples in different freezing regimes had absolute error not exceeding 70C.